Implementation of Vocal Training Methods from the Stanislavski System in the Kanti Becakap - Ikhsan Satria Irianto; Tofan Gustyawan; Lusi Handayani (Universitas Negeri Medan, 2023)
This vocal training method research is an interpretation of Stanislavski's acting method. This study aims to formulate vocal training methods for actors based on the Stanislavski system. The application of this method is carried out in the Kanti Becakap (Art Community). The material object of this research is